Bridging gaps in demographic analysis using phylogenetic imputation - James, T; Salguero-Gomez, R; Jones, O; Childs, D; Beckerman, A (Wiley, 2020)
Population responses to threats such as habitat loss, climate change and overexploitation are usually explored using demographic models parameterized with estimates of vital rates of survival, maturation and fecundity. However, the vital rate estimates required to construct such models are often unavailable, particularly for species of conservation concern. Phylogenetically informed imputation methods have rarely been applied to such demographic data but may be a powerful tool for reconstructing vital rates for vertebrates. Here, we use standardized vital rate estimates for 50 bird species to assess the use of phylogenetic imputation to fill gaps in demographic data. We calculated imputation accuracy for vital rates of focal species excluded from the dataset either singly or in combination, with and without phylogeny, body mass and life history trait data. We used imputed vital rates to calculate demographic metrics, including generation time, to validate the use of imputation in demographic analyses. Covariance among vital rates and other trait data provided a strong basis to guide imputation of missing vital rates in birds, even in the absence of phylogenetic information. Accounting for phylogenetic relationships improved imputation accuracy for vital rates with high phylogenetic signal (Pagel's λ > 0.8). Importantly, including body mass and life history trait data compensated for lack of phylogenetic information. Estimates of demographic metrics were sensitive to the accuracy of imputed vital rates. Accurate demographic data and metrics such as generation time are needed to inform conservation planning processes, for example through IUCN Red List assessments and population viability analysis. Imputed vital rates could be useful in this context but, as for any estimated model parameters, awareness of the sensitivities of demographic model outputs to the imputed vital rates is essential.